Reparatives Denken Lehren aus den Werken von Hasdai Crescas, David Halivni und aus Scriptural Reasoning - Ochs, Peter W. (Mohr Siebeck, 2024)
In an age of global conflict, what forms of reasoning help repair broken relations? We must, says Peter W. Ochs, draw new practices of Reparative Reasoning out of age-old traditions of Scripture-based wisdom. These practices renew age-old relations between mind and heart, science and religion.
PublicationDate: 20240930
Keywords: Jewish Philosophy -- Ibn Rushd (Averroes) -- Repair the World (tikkun olam) -- Abrahamic Religion -- Religion xxxAMPRxxx Science -- Ökotheologie/ecotheology -- Klimakrise/climate crisis -- Religionsphilosophie -- Neuzeit -- Erkenntnistheorie